An Optimal Localization Algorithm of Wireless Sensor Networks - Chunxiang, Wu (International Journal of Online and Biomedical Engineering (iJOE), 2018)
To overcome the low accuracy and high energy consumption of positioning algorithm in wireless sensor network, we proposed a optimization positioning based on algorithm neighborhood model. Based on the characteristics of the neighborhood model, the algorithm selects the best beacon node and calculates the proximity distance to transmit the distance information to the base station. The base station uses the MDS-MAP algorithm to determine the location of the unknown node. The simulation was conducted on NS-2 platform. The results show that the performance of the proposed algorithm was better than traditional optimization algorithms. Significant enhancement is obtained with the proposed algorithm in terms of node distance estimation error and position error.